SAP BusinessObjects Dashboards 4.0 cookbook : over 90 simple and incredibly effective recipes for transforming your business data into exciting dashboards with SAP BusinessObjects Dashboards 4.0 Xcelsius /: over 90 simple and incredibly effective recipes for transforming your business data into exciting dashboards with SAP BusinessObjects Dashboards 4.0 Xcelsius. (2011) - Unknown
No abstract available